ANALISIS PENGGUNAAN BAHASA INDONESIA LARAS HUKUM PADA PUTUSAN PERKARA EKONOMI SYARIAH PENGADILAN AGAMA MAKASSAR - Rustan, Edhy (Al-Amwal : Journal of Islamic Economic Law, 2017)
This study aims to describe the forms of error in using Indonesian language in the legal ruling on sharia economic cases in the Makassar Religious Court. Research is a descriptive qualitative research that is documentative or library research. The data in this study are the use of legal language on the decisions of sharia economic cases number 73 / Pdt.G / 2015 / PA. Mks. Makassar Religious Court. Data collection is done through documentation techniques, by examining a number of references to the use of legal languages, both in the form of books, journals, magazines, newspapers, research reports, and legal documents that are relevant to the problems under study. Recording, namely the author records all matters relating to the phenomenon of legal language usage, which is obtained from the decisions of the Makassar Religious Court and relevant documents, into the notebook prepared in the form of a body of data. The steps of data analysis, namely (1) Identifying the legal language that has experienced an error, (2) Classifying the form of sentence writing errors in the decision of the sharia economic case of the Makassar Religious Court, (3) Analyzing the form of sentence using the Indonesian language in economic case decisions Makassar Islamic sharia, (4) Describe any form of language use error accompanied by descriptions or explanations. The results of the study showed that the Indonesian sentence in the law in the sharia economic decision of the Makassar Religious Court experienced structural errors as a result of not having the function of the subject in sentences, and improper use of conjunctions, and not paying attention to punctuation, diction, ambiguous words, use of redundant words, and adjust the context of the case with the right reasoning pattern. As a result of these errors, the meaning of the sentence becomes ambiguous, making it difficult for the reader to understand. Apart from that, sentence structure errors can cause differences in the meaning that is generated in a decision.